Health geography in New Zealand and Australia: global integration or Antipodean exceptionalism?. (13th February 2019) - Moon, Graham; Kearns, Robin
Abstract: This paper examines the hallmarks of an emergent and distinctive Australian and New Zealand health geography over the last 30 years. Building on an assessment of the early development of the sub‐discipline in the two countries, a review of published work reveals the co‐presence of local themes alongside connections to more global perspectives associated notably with health behaviour. Further common themes are the influence of year‐round exposure to outdoor spaces and the proximity of "blue spaces" to urban centres. However, there are divergences in the evolution of the sub‐discipline. A comparison of attendance at the biennial International Medical Geography Symposia (held since 1985) with publications in the journal Health & Place reveals differentially globalised characters. A steady flow of international visitors and appointments to New Zealand universities as well as more apparent connections to the wider discipline of geography contrast with more applied geospatial and public health connections in Australian health geography.